135k views
2 votes
Solve for n.

–2(n + 2) + 6 = 8

n =

User Ohmu
by
5.0k points

2 Answers

5 votes

Answer:

n = -3

Explanation:

We have the equation –2(n + 2) + 6 = 8. First, we simplify it:

–2(n + 2) + 6 = 8

–2(n + 2) = -2n + (-4) = -2n - 4

So now we have:

-2n - 4 + 6 = 8

We can subtract 6 from both sides of the equation to get:

-2n - 4 = 2

We can also add 4 to both sides to get:

-2n = 6

Divide both sides by 2 to get:

-n = 3

Multiply both sides by -1 to get:

n = -3

User Sgrif
by
4.7k points
2 votes

Answer:

n = -3

Explanation:

Solve for n. –2(n + 2) + 6 = 8 n =-example-1
User Eritbh
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.